2016
DOI: 10.1039/c6cp00593d
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of nanoparticle multiple-ring pattern formation during droplet evaporation with dark-field microscopy

Abstract: Controllable protocols towards nanoparticle self-assembly are important for applications of functional nanomaterials. Evaporation is a simple yet effective method to realize a gold nanoparticle ordered self-assembly, but until now, little attention has been paid to viewing the corresponding assembly process. Herein, with the help of dark-field microscopy, we in situ monitored the whole dynamic process of gold nanorod (GNR) assembly as the solvent evaporated. Differently from the previous coffee-ring effect, ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 50 publications
2
14
0
1
Order By: Relevance
“…It has been reported that the multi-ring pattern is usually made of a solid circle in the center surrounded by many concentric rings, as schematically shown in Figure 1. This phenomenon has indeed been observed experimentally in drying of droplets containing a wide type of solutes, including colloid [1,10,24], polymer [11], DNA [2] and nanoparticles [25].…”
Section: Introductionsupporting
confidence: 57%
“…It has been reported that the multi-ring pattern is usually made of a solid circle in the center surrounded by many concentric rings, as schematically shown in Figure 1. This phenomenon has indeed been observed experimentally in drying of droplets containing a wide type of solutes, including colloid [1,10,24], polymer [11], DNA [2] and nanoparticles [25].…”
Section: Introductionsupporting
confidence: 57%
“…At low concentrations, we observed an unusual combination of dotlike and multi-ring patterns. In their review, Li et al underlined that dotlike patterns were typically observed on hydrophobic substrates, resulting from an evaporation process at constant contact angle with an important contribution of the Marangoni flow that should be oriented radially inward along the substrate and radially outward along the air/liquid interface . Nevertheless, similar patterns, by other names (i.e., “dome”, “coffee eyes”, and “central bump”) were observed on hydrophilic substrates with nanoparticles showing a hydrophobic character (and only at high particle concentration) and with hydrophilic particles deposited on hot substrates or mixed with micrometric particles .…”
Section: Resultsmentioning
confidence: 95%
“…The contact line may even become pinned multiple times, with different pinning strengths, onto the different components that fall out of the solution. This is in addition to the mechanisms for multiple pinning events reported in the literature [34][35][36][37][38] , which mainly consist of multiple deposition events of a single compound or colloidal particle type. The resulting footprint and its topology will in our case consist of several edges of the different deposited materials, effectively being a superposition of several profiles as presented in Fig.…”
Section: Deposit Vs Droplet Propertiesmentioning
confidence: 67%